The prophet Muhammad (PBUH) and urbanization of Madinah - Omer, Spahic (IIUM Press, 2013)
The Islamic theory of general planning and urbanization is as old as the Muslim community. Its fundamental principles have been comprehensively laid in the Holy Qur’an as well as in the sayings and practices of the Prophet Muhammad (pbuh). Certainly, the best example of the earliest Islamic development and city planning was the establishment of the Muslim society in Madinah in the wake of the migration (Hijrah) from Makkah. The matter henceforth was evolving steadily, corresponding with both the rapid spread of Islam throughout the world and the incredible growth of the civilization and cultures inspired by the Islamic worldview and value system. In this book, I attempted to identify and examine some principles of Islamic urban planning and development, which the Prophet (pbuh) under the aegis of revelation had bequeathed to the subsequent Muslim generations. Central to the book are some vital city planning and development issues as advanced by the Islamic perceptions of life, truth, the world, man, space and time, and which the young Muslim mind was then intensively acquainting itself with. The issues discussed are: the philosophy of the Islamic city; the mosque institution; provision of communal facilities and services for al: the relationship between spirituality and development; peaceful coexistence with the environment; housing; the marketplace; and open spaces. By exploring these subjects, the strength and soundness of the fundamentals of the first Muslim community clearly come into sight, as does the visionary disposition of the Prophet (pbuh) to development, leadership, sustainability and management. The period covered by this study is the one which the first Muslims had spent in Madinah subsequent to the Hijrah, about the last ten years of the Prophet’s heavenly mission. Studying this particular epoch from the perspective of urban planning and development is of great importance, because at the time of the Hijrah the ongoing revelation of Islam was already about thirteen years old and the Muslims were yet to set up a free and autonomous state of their own. Once the city of Madinah with most of its inhabitants wholeheartedly welcomed the new religion - so fiercely disapproved of by many where it had originated, i.e., in Makkah - the wait finally came to an end and the stage was set for broadening the focus of the nascent community’s undertakings. As a result, the focus of revelation was widened too. The religion of Islam thus began to assert itself as a universal code of life overlooking no segment of human existence, after having been portrayed essentially as an inclusive belief system during the entire precarious Makkan episode. From the perspectives of urbanization, general planning and development, the entire Madinah period -- the first half in particular -- was exceptionally eventful. This book aims, firstly, to help its readers identify and understand the essence, purpose and origins of the Islamic theory of general planning, development and urbanization; secondly, to help its readers understand, appreciate and promote the extent of the Prophet’s interest in the idea of urbanization and its noble objectives; and thirdly, to play a part in clarifying and doing away with some pervasive misconceptions and misunderstandings about Islam and its Prophet (pbuh), in general, and about the nature and achievements of the early Muslim community in Madinah, in particular.